Variations in the Wave Climate and Sediment Transport Due to Climate Change along the Coast of Vietnam - Dastgheib, Ali; Reyns, Johan; Thammasittirong, Supot; Weesakul, Sutat; Thatcher, Marcus; Ranasinghe, Roshanka (Journal of marine science and engineering, 2016)
This study quantifies the climate change (CC)-driven variations in wave characteristics and the resulting variations in potential longshore sediment transport rate along the ~2000 km mainland coast of Vietnam. Wind fields derived from global circulation models (GCM) for current and future (2041–2060 and 2081–2100) climate conditions are used to force a numerical wave model (MIKE21 SW) to derive the deep water wave climate. The offshore wave climate is translated to nearshore wave conditions using another numerical model (Simulating WAves Nearshore—SWAN) and finally, a sediment transport model (GENEralized model for Simulating Shoreline Change—GENESIS) is used to estimate potential sediment transport for current and future climate conditions. Results indicate that CC effects are substantially different in the northern, central and southern parts of the coast of Vietnam. The 2081–2100 mean significant wave height along the northern coast is estimated to be up to 8 cm lower (relative to 1981–2000), while projections for central and southern coasts of Vietnam indicate slightly higher (increases of up to 5 cm and 7 cm respectively). Wave direction along the northern coast of Vietnam is projected to shift by up to 4° towards the south (clockwise) by 2081–2100 (relative to 1981–2000), up to 6° clockwise along the central coast and by up to 8° anti-clockwise (to the north) along the southern coast. The projected potential longshore sediment transport rates show very substantial and spatially variable future changes in net transport rates along the coast of Vietnam, with increases of up to 0.5 million m3/year at some locations (by 2081–2100 relative to 1981–2000), implying major changes in future coastline position and/or orientation. The vicinity of the highly developed city of Da Nang is likely to be particularly subject to coastline changes, with potentially an additional 875,000 m3 of sand being transported away from the area per year by the turn of the 21st century.